The Creation of the Free Exchange Zone– a Step Towards Integration of the Republic of Moldova to the European Union - Gherasim Ruslan (CES Working Papers, 2012)
The trade of the Republic of Moldova in a large extent depends on the exports and imports to/from the European Union. The EU enlargement phenomenon is placing the Republic of Moldova on a favorable position, if speaking about the negotiation of the terms and conditions for goods and services export and import. The Free Trade Area between the Republic of Moldova and the EU will constitute an important step towards the integration of the Republic of Moldova into the European economic space and the economic development of the country as well.
Keywords: F15; F19; F59; 330; Exchange zone; integration; Generalized System of Preferences; trade diversion Romania